1991
DOI: 10.1097/00006842-199107000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The relation between dominance, anger, and hormones in normally aging men: results from the Massachusetts Male Aging Study.

Abstract: This paper examines the relation of two personality characteristics (dominance and anger) to hormones in normally aging men. The relation of the Jackson Personality Research Form E Dominance subscale and the Spielberger Anger Expression scale to serum levels of 17 endocrine variables, including testosterone (T) and dihydrotestosterone (DHT), cortisol, and prolactin, was examined in 1709 men aged 39 to 70 years randomly sampled from the Boston Metropolitan Statistical Area. Canonical correlation analysis result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(44 citation statements)
references
References 37 publications
2
40
0
2
Order By: Relevance
“…In accordance with previous studies (Gettler et al, 2011;A. Gray, Jackson, & McKinlay, 1991;Mehta, Jones, & Josephs, 2008;Mehta & Josephs, 2010;Popma et al, 2007), testosterone and cortisol levels were modestly correlated (r = .22, p = .008).…”
Section: Descriptive Statistics and Zero-order Correlationssupporting
confidence: 92%
“…In accordance with previous studies (Gettler et al, 2011;A. Gray, Jackson, & McKinlay, 1991;Mehta, Jones, & Josephs, 2008;Mehta & Josephs, 2010;Popma et al, 2007), testosterone and cortisol levels were modestly correlated (r = .22, p = .008).…”
Section: Descriptive Statistics and Zero-order Correlationssupporting
confidence: 92%
“…The basis for this ongoing study was a meta-analysis of 44 publications dealing with the interaction of aging and testosterone levels [4]. The data demonstrated a decline in serum testosterone with age as well as an important influence of the individual health status and corresponding medication on serum testosterone levels [4].…”
Section: Sexuality Of the Elderly Hormonal Alterations Of Agingmentioning
confidence: 99%
“…In healthy men, serum testosterone levels vary between 11 and 40 mmol/l; these levels decrease by about 30 % between the ages of 25 and 75 years [4,6]. Most of the circulating serum testosterone is bound to albumin or sex hormone-binding globulin (SHBG).…”
Section: Sexuality Of the Elderly Hormonal Alterations Of Agingmentioning
confidence: 99%
“…From this perspective, the anger leads to occurrence of aggressive reactions when it is not expressed in a healthy or constructive manner (Berkowitz, 1990;Ellis, 1997). Likewise, the literature points out that high level of anger is associated with aggressiveness (Gray, Jackson, & McKinlay, 1991), and the high level of anger is associated with aggressiveness and tendency to perpetration in the individuals that have committed a crime (McDougall, Venables, & Roger, 1991). It is reported that the concepts of guilt and shyness are significantly associated with high level of anger and aggressiveness (Tangney, Wagner, Fletcher, & Gramzov, 1992;Fine & Olson, 1997) in the university students.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%